2012
DOI: 10.1136/bmjopen-2012-001651
|View full text |Cite
|
Sign up to set email alerts
|

Hospital episode statistics: improving the quality and value of hospital data: a national internet e-survey of hospital consultants

Abstract: HypothesisSenior hospital clinicians are poorly engaged with clinical coding and hospital episode statistics (HES).Aims ▸ To understand the current level of clinical engagement with collection of national data and clinical coding.▸ To gain the views of frontline staff on proposed improvements to hospital statistics.▸ To gain an indication of likely clinical engagement in change.▸ To understand the clinical priority for improvement.DesignInternet e-survey accessible from Academy of Royal Medical College Website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 8 publications
0
48
1
Order By: Relevance
“…A national audit of a large UK trust into clinical coding revealed that in orthopaedics 20% of diagnosis and 19% of procedures are coded inaccurately 25. Therefore, although we employed a robust method to identify ankle replacement more accurately, the actual identification of PE was still limited by accuracy of clinical coding.…”
Section: Discussionmentioning
confidence: 99%
“…A national audit of a large UK trust into clinical coding revealed that in orthopaedics 20% of diagnosis and 19% of procedures are coded inaccurately 25. Therefore, although we employed a robust method to identify ankle replacement more accurately, the actual identification of PE was still limited by accuracy of clinical coding.…”
Section: Discussionmentioning
confidence: 99%
“…Coded data are a poor reflection of clinical practice, though this has improved in the last decade 19 20. In this study, only 34 out of 108 (31%) eligible episodes identified from AERs were recorded using the code for diabetes-related emergency calls.…”
Section: Discussionmentioning
confidence: 99%
“…HES is a database that contains details of all ED attendances, hospital admissions and outpatient appointments at all NHS hospitals across the whole of England 19. The main purpose of HES data is to allow hospitals to be paid for the care they deliver.…”
Section: Methodsmentioning
confidence: 99%
“…While HES is derived directly from hospital's own data submissions for PbR, the quality and utility of these data have been subject to the reports of substantial missing data, inconsistent coding and poor data definitions 22 23. The Academy of Royal Medical Colleges has recently called for a number of improvements so that clinicians become more engaged with the collection of national data 24. In neonatal medicine, the availability of high-quality data captured at the point of care by clinical teams has led clinicians to ignore HES neonatal data.…”
Section: Hospital Episode Statisticsmentioning
confidence: 99%